North Atlantic Oscillation polarity during the past 3000 years derived from sediments of a large lowland lake, Schweriner See, in NE Germany - Adolph, Marie-Luise; Czerwiński, Sambor; Dreßler, Mirko; Strobel, Paul; Bliedtner, Marcel; Lorenz, Sebastian; Debret, Maxime; Haberzettl, Torsten (Climate of the Past, 2024)
Based on a multi-dating and multi-proxy approach, we reconstruct Late Holocene environmental changes derived from sediments of Schweriner See, a large lowland lake in NE Germany, covering the past 3070 + 170 / - 210 years cal BP. We infer variations in large-scale atmospheric circulation systems by combining in-lake productivity indicators obtained from traditional and high-resolution techniques (e.g. LOI 550 , TOC, inc / coh), diatom assemblages, and compound-specific hydrogen isotopes ( δ 2 H C 25 ). Before 105 + 95 / - 75 cal BP ( ∼ 1850 CE), changes in productivity and the occurrence or disappearance of the diatom species Stephanocostis chantaicus reflect winter temperature variability, while variations in the compound-specific hydrogen isotopes suggest changes in the moisture source region. We observe distinct variations between (i) milder winter temperatures with a moisture source region in the southern–central North Atlantic and (ii) colder winter temperatures with a moisture source in the northern North Atlantic and/or Arctic regions. Such distinct variations in winter temperature and moisture source region are mainly modulated by the North Atlantic Oscillation (NAO). This affects, among others, westerly wind strength and pathways and, thereby, winter temperature and moisture source region for northern central Europe. Besides these long-term shifts in atmospheric conditions, short-term variations in titanium can be linked to lake-level variability, most likely influenced by changes in precipitation and/or evaporation, and after the 12th century to anthropogenic impacts. Since 105 + 95 / - 75 cal BP ( ∼ 1850 CE), productivity has been driven predominantly by nutrient availability related to anthropogenic activities masking the hydroclimatic signal.